Electrophysiological response of Bactrocera oleae (Rossi) (Diptera: Tephritidae) adults to olive leaves essential oils from different cultivars and olive tree volatiles - Malheiro, Ricardo (2016)
In the present study, the electrophysiological response of olive fly adults, Bactrocera oleae (Rossi), to oliveleaves essential oils (EO’s) from different cultivars (cvs. Cobrançosa, Madural and Verdeal Transmontana) with distinct fly susceptibility degrees, as well as host volatiles ([(E)-2-hexenal, α-pinene, farnesene, xylene, and nonanal]) and semiochemicals (spiroketal, and (Z)-9-tricosene) were assessed at differentadults ages ([0–5] days old, early young adults; [5–10] days old, corresponding to sexual maturity; and[10–15] days old, when females are gravid).Results showed clear differences in the EAG response of both sexes to EO’s of the different cultivars, with higher signal in cv. Cobrançosa, the less susceptible to olive fly. An inverse proportionality was found between the EAG response to EO’s in both sexes and the susceptibility degrees to olive fly. Chemical composition of EO’s proved to be highly influenced by olive cultivars, with a clear differentiation between them. A possible deterrent mechanism could be involved in the observed results. Host volatiles, mainly (E)-2-hexenal and nonanal exerted higher EAG responses, (E)-2-hexenal mainly in females at sexual maturity and oviposition period, while nonanal elicited higher responses at [5–10]days old in males, corresponding to sexual maturity. The present results give important results regarding olive fly oviposition preference as well to olive fly-olive tree interactions.